2021
DOI: 10.3390/ijerph182412988
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Work Ability Index in Health Centre Workers in Spain

Abstract: The aim of the present study is to analyse the psychometric properties of the work ability index (WAI) within a sample of Spanish health centre workers. The WAI was translated into Spanish using transcultural and forward–backward translation processes and administered to 1184 Spanish health centre workers. Internal consistency, predictive validity, and discriminative ability were examined. Exploratory factor analysis, via principal components analysis and confirmatory factor analysis, determined the most appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 33 publications
(46 reference statements)
4
23
1
Order By: Relevance
“…In 2060, the size of the elderly population, i.e., those aged more than 65, is predicted to rise from 13% today to 31% [2]. This trend is consistent with a previous study by Fischer et al, (2021) [3], Nygaard et al, (2021) [4], and Rodríguez and colleagues (2021) [5], who concluded that the workforce is aging in many countries around the world. There is strong evidence demonstrating that fast changes in the nature of work and technology will require workers with new skills to fill labor market needs created by population aging [2].…”
Section: Introductionsupporting
confidence: 86%
“…In 2060, the size of the elderly population, i.e., those aged more than 65, is predicted to rise from 13% today to 31% [2]. This trend is consistent with a previous study by Fischer et al, (2021) [3], Nygaard et al, (2021) [4], and Rodríguez and colleagues (2021) [5], who concluded that the workforce is aging in many countries around the world. There is strong evidence demonstrating that fast changes in the nature of work and technology will require workers with new skills to fill labor market needs created by population aging [2].…”
Section: Introductionsupporting
confidence: 86%
“…The results regarding gender differences vary, some research with HCWs show that men have better WAI scores than women (Cotrim et al, 2011, Cotrim et al, 2014Mateo-Rodríguez et al, 2021a), but a systematic literature review by Van den Berg et al (2008) does not show any association between gender and WAI as defined by current study, too.…”
Section: Discussioncontrasting
confidence: 49%
“…The rapid ageing of the workforce is reflected in an estimated share of HCWs who were aged 55 years or over (Eurostat, 2019). Increasing interest has been shown in the possibilities of extending working lives, the influence of ageing on Occupational Health and Safety, and on the Work Ability Index (Bohle et al, 2010;Smyth et al, 2018;Martinez & Fischer, 2019;Varianou-Mikellidou et al, 2019;Mateo-Rodríguez et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended as a diagnostic instrument for the development of measures for health support and the identification of employees who require medical care 38,39 . WAI has been well used in academic and clinical settings, with a reliability value of 0.73 40–42 . The WAI measures seven aspects of WA: current WA compared with the lifetime best; WA in relation to the demands of the job; number of current diseases diagnosed by physician; estimated work impairment due to diseases; sick leave during the past year (12 months); own prognosis of work ability 2 years from now; and mental capacities 36 .…”
Section: Methodsmentioning
confidence: 99%
“…38,39 WAI has been well used in academic and clinical settings, with a reliability value of 0.73. [40][41][42] The WAI measures seven aspects of WA: current WA compared with the lifetime best; WA in relation to the demands of the job; number of current diseases diagnosed by physician; estimated work impairment due to diseases; sick leave during the past year (12 months); own prognosis of work ability 2 years from now; and mental capacities. 36 The maximum score on the index is 49 points, and the minimum is 7.…”
Section: Instrumentationmentioning
confidence: 99%